The death penalty in Iran - Schabas, William (The Elgar companion to capital punishment and society, 2024)
Iran is probably the country with the world’s highest rate of execution. The death penalty can be imposed for a broad range of crimes, although most cases involve drug-related crimes or murder. The number of executions declined in the mid-2010s following amendments to drug legislation, but the reduction was only temporary. In cases of murder, the family of the victim participates in the penalty phase, with the right to insist on capital punishment unless the perpetrator provides ‘blood money’. Iran is one of the few countries to permit public executions. It also allows execution of individuals who were under the age of 18 at the time of the crime. Iran is in quite flagrant conflict with international legal obligations it has assumed with respect to capital punishment.